Marx's theory of alienation and the commodification of water in South Africa - Grant, Matthew (Department of Sociology, 2014)
This dissertation uses Marx's theory of alienation in seeking to give a fuller understanding of the commodification of domestic water. As such, it also focuses on the socio-historical process of the provision of water through privatisation in the dominant mode of production: capitalism in its neoliberal phase.